Strategy for Strengthening Community Organizational Behavior in Supporting the National Food Security Program: Study of the Putri Rahayu Women's Farmers Group - Ulva Roifatul Lailin; Putri Cinta Mei (Journal of Public Policy, Governance and Local Government, 2026)
Community-based women farmers’ groups play a strategic role in strengthening local food security by serving as non-governmental actors that support public service delivery in food production and community empowerment. This study examines the organizational dynamics of the Putri Rahayu Women Farmers Group in Bendogerit Subdistrict, Blitar, with the aim of identifying strategies to enhance organizational behavior and improve program effectiveness and sustainability. The research specifically focuses on three key dimensions of organizational management: communication, leadership, and member participation. A descriptive qualitative approach was employed, using in-depth interviews, participatory observation, and document analysis to explore the internal governance system and assess both institutional strengths and operational challenges. The findings reveal that although the group possesses a strong social foundation and collective commitment, it continues to face significant obstacles related to internal coordination, limited managerial capacity, and insufficient external policy support. To address these issues, the study recommends strengthening leadership competencies through capacity-building programs, improving communication mechanisms, increasing member involvement in participatory planning, and expanding collaborative partnerships with government agencies, non-governmental organizations, and private sector actors to improve access to resources and market opportunities. The study contributes to the development of community-based organizational governance models by emphasizing the application of Good Governance principles, including accountability, transparency, participation, and effectiveness, as essential foundations for sustainable women’s empowerment and resilient local food security systems.